TAVSHEDENS PRAKSIS OG LIDELSENS PROSA - Jackson, Michael (Tidsskriftet Antropologi, 2002)
The subject of this article is suffering – how it is borne and how it is explained – by people in very different circumstances. The author begins by recounting a young Sierra Leonean woman’s story about her wartime suffering and her postwar situation. He then turns to consider the kind of suffering “at a distance” liberal Westerners are wont to experience when confronted by the pain, distress, and misery of others, and finding ourselves at a loss to do anything about it. Finally, the author returns to discuss the way Sierra Leoneans address the suffering of war, offering a critique of the way suffering is commonly construed in the affluent West. The article contemplates how Western reactions to the suffering of others tend to involve a narcissistic focus on one’s inner feelings and thoughts, including one’s feelings for and intellectual reflections on the plight of others. In contrast, the Kuranko in Sierra Leone are less prone to fantasise rescue or salvation, or hope for a world in which there is no pain and rather respond to the suffering with resignation and silence. Such silence may be a way of healing and reconciliation, and not a way of evading or repressing an issue. The anthropology of suffering should therefore evade the Western tendency of excessive verbalising. It can, argues the author, only do justice to suffering by examining each situation as if there were no universal measure against which to judge it, only various points of view that must be taken into account in exploring it.